Magnetic Field-Assisted Fission of a Ferrofluid Droplet for Large-Scale Droplet Generation - Zhao, Haibo (Langmuir : the ACS journal of surfaces and colloids, 2022)
With the presence of an external magnetic field, a ferrofluid droplet exhibits a rich variety of interesting phenomena notably different from nonmagnetic droplets. Here, a ferrofluid droplet impacting on a liquid-repellent surface is systematically investigated using high-speed imaging. The pre- and post-impact, including the droplet stretching, maximum spreading diameter, and final impact modes, are shown to depend on the impact velocity and the magnitude of the external magnetic field. A scaling relation involving the Weber and magnetic Bond numbers is fitted to predict the maximum spreading diameter based on the magnetic field-induced effective surface tension. The impact outcome is also investigated and classified into three patterns depending on the occurrence of the rim interface instability and the fission phenomenon. Two types of fission (i.e., evenly and unevenly distributed sizes of the daughter droplets) are first identified, and the corresponding mechanism is revealed. Last, according to Rayleigh-Taylor instability, a semiempirical formula is proposed to estimate the number of the daughter droplets in the regime of evenly distributed size, which agrees well with the experimental data. The present study can provide more insight into large-scale droplet generation with monodispersive sizes